2019
DOI: 10.1038/s41598-019-52058-z
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebroventricular injection of ouabain causes mania-like behavior in mice through D2 receptor activation

Abstract: Intracerebroventricular (ICV) administration of ouabain, an inhibitor of the Na, K-ATPase, is an approach used to study the physiological functions of the Na, K-ATPase and cardiotonic steroids in the central nervous system, known to cause mania-like hyperactivity in rats. We describe a mouse model of ouabain-induced mania-like behavior. ICV administration of 0.5 µl of 50 µM (25 pmol, 14.6 ng) ouabain into each lateral brain ventricle results in increased locomotor activity, stereotypical behavior, and decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 56 publications
(75 reference statements)
1
17
0
5
Order By: Relevance
“…Consequently, numerous studies have proposed promising strategies to improve the delivery of therapeutic agents to the brain by circumventing or overcoming the BBB during the last decades. These strategies include intracerebroventricular injections (Lopachev et al, 2019), convection enhanced delivery (Zhan and Wang, 2018), inhibition of efflux transporters (Sanchez-Covarrubias et al, 2014), chemical modification (Al-Ahmady, 2018), and the application of hyperosmotic agents (Patel et al, 2009) or focused ultrasound (Dauba et al, 2020;Lin et al, 2020;Wu et al, 2021a), and so on. However, the limitation of these administration routes is marred by safety concerns, invasive, and erratic efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, numerous studies have proposed promising strategies to improve the delivery of therapeutic agents to the brain by circumventing or overcoming the BBB during the last decades. These strategies include intracerebroventricular injections (Lopachev et al, 2019), convection enhanced delivery (Zhan and Wang, 2018), inhibition of efflux transporters (Sanchez-Covarrubias et al, 2014), chemical modification (Al-Ahmady, 2018), and the application of hyperosmotic agents (Patel et al, 2009) or focused ultrasound (Dauba et al, 2020;Lin et al, 2020;Wu et al, 2021a), and so on. However, the limitation of these administration routes is marred by safety concerns, invasive, and erratic efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…CTS are considered to be endogenous regulators, or hormone-like compounds [ 1 , 2 , 17 , 18 , 19 ]. It is known that CTS can significantly affect dopamine neurotransmission through affecting the function of DAT or dopamine receptors [ 20 , 21 ]. Intracerebroventricular (ICV) CTS injection causes bipolar disorder-like behavior in rodents [ 21 , 22 ], which may be accompanied by neuron damage [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that CTS can significantly affect dopamine neurotransmission through affecting the function of DAT or dopamine receptors [ 20 , 21 ]. Intracerebroventricular (ICV) CTS injection causes bipolar disorder-like behavior in rodents [ 21 , 22 ], which may be accompanied by neuron damage [ 22 , 23 ]. In the amphetamine mania model in rats it was shown that intracerebroventricular injection of CTS antibodies neutralizes the effects of amphetamine administration [ 24 ] which means that not only exogenous but also endogenous CTS may contribute to mania-like behavior.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations